y=sinx-√3cosx=2xin(x-∏/3)怎么算得出2xin(x-∏/3)?
y=sinx-√3cosx=2xin(x-∏/3)怎么算得出2xin(x-∏/3)?
∫(sinx)^3(cosx)^5dx
∫(sinx)^3(cosx)^5dx
y=3cosx是基本初等函数.
y=3cosx是基本初等函数.
()'=cosx A: sinx B: cosx C: -sinx D: -cosx
()'=cosx A: sinx B: cosx C: -sinx D: -cosx
已知y=cosx,则y'=() A: sinx B: cosx C: -sinx D: -cosx
已知y=cosx,则y'=() A: sinx B: cosx C: -sinx D: -cosx
设f(x)可导,且y=f(cosx),则dy/dx等于( )。 A: -f'(cosx)sinx B: cosx.f'(cosx) C: f'(cosx) D: f'(x)cosx
设f(x)可导,且y=f(cosx),则dy/dx等于( )。 A: -f'(cosx)sinx B: cosx.f'(cosx) C: f'(cosx) D: f'(x)cosx
(cosx)' A: sinx B: -sinx C: -cosx
(cosx)' A: sinx B: -sinx C: -cosx
函数y=cosx的导函数为 ( )。 A: sinx B: cosx C: -cosx D: -sinx
函数y=cosx的导函数为 ( )。 A: sinx B: cosx C: -cosx D: -sinx
下列函数中,cosx的导数是( ). A: -cosx B: -sinx C: cosx D: sinx
下列函数中,cosx的导数是( ). A: -cosx B: -sinx C: cosx D: sinx
设f(x)=cosx,则f(-cosx)=______.
设f(x)=cosx,则f(-cosx)=______.